Systemic Lupus Erythematosus With Isolated Psychiatric Symptoms and Antinuclear Antibody Detection in the Cerebrospinal Fluid - Lüngen, Eva M.; Maier, Viktoria; Venhoff, Nils; Salzer, Ulrich; Dersch, Rick; Berger, Benjamin; Riering, Anne N.; Nickel, Kathrin; Fiebich, Bernd L.; Süß, Patrick; Maier, Simon J.; Egger, Karl; et al. (Frontiers in Psychiatry, 2019)
Background: Organic psychiatric disorders can be caused by immunological disorders, such as autoimmune encephalitis or systemic lupus erythematosus (SLE). SLE can affect most organs, as well as the central nervous system (CNS). In this paper, we describe a patient with an isolated psychiatric syndrome in the context of SLE and discuss the role of antibody detection in the cerebrospinal fluid (CSF). Case presentation: The 22-year-old German male high school graduate presented with obsessive-compulsive and schizophreniform symptoms. He first experienced obsessive-compulsive symptoms at the age of 14. At the age of 19, his obsessive thoughts, hallucinations, diffuse anxiety, depressed mood, severe dizziness, and suicidal ideation became severe and did not respond to neuroleptic or antidepressant treatment. Due to increased antinuclear antibodies (ANAs) with anti-nucleosome specificity in serum and CSF, complement activation, multiple bilateral white matter lesions, and inflammatory CSF alterations, we classified the complex syndrome as an isolated psychiatric variant of SLE. Immunosuppressive treatment with two times high-dose steroids, methotrexate, and hydroxychloroquine led to a slow but convincing improvement. Conclusion: Some patients with psychiatric syndromes and increased ANA titers may suffer from psychiatric variants of SLE, even if the American College of Rheumatology criteria for SLE are not met. Whether the psychiatric symptoms in our patient represent a prodromal stage with the later manifestation of full-blown SLE or a subtype of SLE with isolated CNS involvement remains unclear. Regardless, early diagnosis and initiation of immunosuppressive treatment are essential steps in preventing further disease progression and organ damage. Intrathecal ANAs with extractable nuclear antigen differentiation may be a more sensitive marker of CNS involvement compared with serum analyses alone.